An Armored Mixed Conductor Interphase on a Dendrite‐Free Lithium‐Metal Anode - Yan, Chong; Cheng, Xin‐Bing; Yao, Yu‐Xing; Shen, Xin; Li, Bo‐Quan; Li, Wen‐Jun; Zhang, Rui; Huang, Jia‐Qi; Li, Hong; Zhang, Qiang (Advanced materials (Weinheim), 2018)
Lithium‐metal electrodes have undergone a comprehensive renaissance to meet the requirements of high‐energy‐density batteries due to their lowest electrode potential and the very high theoretical capacity. Unfortunately, the unstable interface between lithium and nonaqueous electrolyte induces dendritic Li and low Coulombic efficiency during repeated Li plating/stripping, which is one of the huge obstacles toward practical lithium‐metal batteries. Here, a composite mixed ionic/electronic conductor interphase (MCI) is formed on the surface of Li by in situ chemical reactions of a copper‐fluoride‐based solution and Li metal at room temperature. The as‐obtained MCI film acts like the armor of a soldier to protect the Li‐metal anode by its prioritized lithium storage, high ionic conductivity, and high Young's modulus. The armored MCI can effectively suppress Li‐dendrite growth and work effectively in LiNi0.5Co0.2Mn0.3O2/Li cells. The armored MCI presents fresh insights into the formation and regulation of the stable electrode–electrolyte interface and an effective strategy to protect Li‐metal anodes in working Li‐metal batteries. A composite mixed ionic/electronic conductor interphase (MCI) is formed on the surface of lithium by in situ chemical reactions of copper‐fluoride‐based solution and Li metal at room temperature. The as‐obtained MCI film acts like the armor of a soldier to protect the Li‐metal anode by its prioritized lithium storage, high ionic conductivity, and high Young's modulus.